Extracellular vesicles in hepatocellular carcinoma: unraveling immunological mechanisms for enhanced diagnosis and overcoming drug resistance - Su, Lanqian; Yue, Yuxin; Yan, Yalan; Sun, Jianming; Meng, Lanxin; Lu, Jiaan; Zhang, Lanyue; Liu, Jie; Chi, Hao; Liu, Sinian; Yang, Zhongqiu; Tang, Xiaowei (Frontiers in Immunology, 2024)
Current research is focused on utilizing EVs as a biopsy tool to improve the diagnostic accuracy of HCC, reduce surgical risk, and explore their potential in modulating drug resistance and advancing immunotherapeutic strategies. Extracellular vesicles (EVs) have been increasingly recognized as important non-invasive biomarkers in hepatocellular carcinoma (HCC) due to the presence of a variety of biomolecules within them, such as proteins and RNAs, etc. EVs play a key role in the early detection, diagnosis, treatment, and prognostic monitoring of HCC. These vesicles influence the development of HCC and therapeutic response in a variety of ways, including influencing the tumor microenvironment, modulating drug resistance, and participating in immune regulatory mechanisms. In addition, specific molecules such as miRNAs and specific proteins in EVs are regarded as potential markers for monitoring treatment response and recurrence of HCC, which have certain research space and development prospects. In this paper, we summarize the aspects of EVs as HCC diagnostic and drug resistance markers, and also discuss the questions that may be faced in the development of EVs as markers.